A tale dark & Grimm - Gidwitz, Adam.; Grimm, Jacob, 1785-1863.; Grimm, Wilhelm, 1786-1859. (New York : Puffin Books, 2011)
Follows Hansel and Gretel as they walk out of their own story and into eight more tales, encountering such wicked creatures as witches, along with kindly strangers and other helpful folk. Based in part on the Grimms' fairy tales Faithful Johannes, Hansel and Gretel, The seven ravens, Brother and sister, The robber bridegroom, and The devil and his three golden hairs.
Notable/Best Books (A.L.A.)
Pub Weekly
School Library Journal starred
Booklist, November 2010
Bulletin (Center for Children's books), December 2010
Horn Book, January 2011
Keywords: Brothers and sisters -- Juvenile fiction; Characters and characteristics in literature -- Juvenile fiction; Fairy tales; Brothers and sisters -- Fiction; Characters in literature -- Fiction; Fairy tales; Characters and characteristics in literature -- Fiction; Fairy tales; Siblings -- Fiction